2022
DOI: 10.1017/s1047951121004698
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocarditis following COVID-19 mRNA vaccination: a paediatric case

Abstract: Myocarditis is an inflammation of the heart muscle. In this case, a previously healthy, 17-year-old adolescent with myocarditis after BNT162b2 mRNA vaccination was reported. He was admitted to the hospital with severe chest pain, changes in electrocardiography, and elevation in serum troponin level after fourth day of receiving first dose of vaccine. There was no coronary arterial disease in coronary angiogram. A diagnosis of vaccine-induced myocarditis was made, and supportive treatment was initiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…A total of 100 case reports or case series which reported cardiac complications after COVID-19 vaccination were included 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 100 case reports or case series which reported cardiac complications after COVID-19 vaccination were included 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , …”
Section: Resultsmentioning
confidence: 99%
“…Another case series study reported 9 cases of acute pericarditis of them seven received mRNA vaccines BNT162b2 and mRNA-1273, and 2 cases received AZD1222 99 . Several more case-report studies documented myocarditis or recurrence of acute myocarditis after receiving mRNA vaccination against COVID-19 infection 5 , 7 , 8 , 9 , 10 , 11 , 17 , 18 , 20 , 22 , 24 , 37 , 38 , 39 , 41 , 42 , 43 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 71 , 72 , 75 , 77 , 80 , 81 , 83 , 88 , 90 , 91 , 98 , 109 , 110 , 123 . Myocarditis was reported to be more common in patients who received the COVID-19 mRNA vaccine versus the non-mRNA vaccine, and it was also more common in patients who received the vaccine for the second time.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 27 studies included in our systematic review, 8 were observational studies while 19 were case reports and case series. In particular, we included the following: 7 paediatric case reports, 13 , 14 , 15 , 16 , 17 , 18 , 19 6 paediatric case series, 20 , 21 , 22 , 23 , 24 , 25 6 mixed case series, including both adolescent and adult patients in which we collected only cases ≤18 years. 26 , 27 , 28 , 29 , 30 , 31 Analysing all these reports, we summarised cases of hospitalised myocarditis following COVID‐19 vaccination among adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…In the United States (US), two messenger RNA (mRNA) coronavirus disease 2019 (COVID-19) vaccines, BNT162b2 mRNA (Pfizer-BioNTech) and mRNA-1273 (Moderna) were granted emergency use authorization (EUA) by the US Food and Drug Administration (FDA) in December 2020 (1,2). With the increasing number of administered COVID-19 mRNA vaccines, growing evidence for myocarditis and pericarditis as rare complications after COVID-19 mRNA vaccination has been reported, especially in young adult and adolescent males (3)(4)(5)(6)(7)(8)(9)(10). Recently, the Advisory Committee on Immunization Practices (ACIP) of Centers for Disease Control (CDC) identified a likely association between COVID-19 mRNA vaccines and cases of myocarditis/pericarditis (11).…”
Section: Introductionmentioning
confidence: 99%